Tetrazine-trans-Cyclooctene Ligation for the Rapid Construction of (18)F Labeled Probes - Li, Zibo (2010)
A radiolabeling method for bioconjugation based on the Diels-Alder reaction between 3,6-diaryl-s-tetrazines and an (18)F-labeled trans-cyclooctene is described. The reaction proceeds with exceptionally fast rates, making it an effective conjugation method within seconds at low micromolar concentrations.